Formulations and standardization of the aqueous extract from the leaves of Morinda lucida Benth, a hypoglycemating plant - AGBOKPONTO, JANVIER ENGELBERT; ASSANHOU, Assogba Gabin (My University, 2022)
With a view to enhancing endogenous knowledge about plants, the present study has been aimed at developing and standardizing dosage forms based on the aqueous extract of Morinda lucida Benth, a plant with hypoglycaemic anti-hyperglycaemic properties. After the aqueous extraction of the leaves of this plant, by maceration, phytochemical screening was carried out on a TLC plate by using the method of Wagner and Bladt (1996) then three capsule formulations were produced (F1, F2 and F3). Different pharmacotechnical tests were conducted according to the European Pharmacopoeia (Eur. Ph.). The presence of alkaloids, flavonoids and saponosids in the aqueous extract attests to its hypoglycaemic and anti-hyperglycaemic properties. Likewise, their presence in the capsules gives them these same properties and shows the neutrality of the used excipients on the phytochemical’s compounds of the extract. The average capsule masses are 190.525 mg, 250.04 mg, and 381.54 mg, respectively, for the formulas F1, F2, and F3 capsules. The polyphenols that were used as a tracker in the aqueous extract did not show a good dissolution profile in milliQ water, which would be due to their complexation by gelatine or to their decomposition after dissolution in the medium, however, it was observed a dissolution in accordance with the specifications in 0.1 M hydrochloric acid. The formula F3 is that which complies with all the Eur. Phspecifications and could be recommended for preclinical testing in order to use as Morinda lucida Benth leaves substitute.
Keywords: Plant; Morinda lucida Benth; Hypoglycaemia; Aqueous extract; capsule